"Cloud in trousers": presentation and noted translation of the second part of the poem - Mei, Letícia Pedreira (RUS (Sao Paulo), 2020)
We introduce Vladimir Mayakovsky’s lyrical long poem Cloud in Trousers (1915) and propose a poetic and noted translation of its second part — which aims at criticizing the art of his time — from Russian to Brazilian Portuguese.